2008
DOI: 10.1101/lm.866408
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel, an NF-κB family transcription factor, is required for hippocampal long-term synaptic plasticity and memory formation

Abstract: Transcription is a critical component for consolidation of long-term memory. However, relatively few transcriptional mechanisms have been identified for the regulation of gene expression in memory formation. In the current study, we investigated the activity of one specific member of the NF-B transcription factor family, c-Rel, during memory consolidation. We found that contextual fear conditioning elicited a time-dependent increase in nuclear c-Rel levels in area CA1 and DG of hippocampus. These results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 71 publications
(101 reference statements)
4
118
0
Order By: Relevance
“…In Aplysia, PARP-1 activation is required for the transcription of ribosomal RNAs and ribosomal proteins (Hernández et al, 2009). Conversely, NF-Band CREB-dependent gene expression is required for learning and memory stabilization in mammals (Barco et al, 2002;Levenson et al, 2004b;Vecsey et al, 2007;Ahn et al, 2008;Fontán-Lozano et al, 2009) (for review, see Alberini, 2009). Our gene expression analysis in the hippocampus after OR training demonstrated the increase in NF-B and CREB gene targets and, in both cases, training-induced NF-B-and CREB-dependent gene expression required of PARP-1 activation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In Aplysia, PARP-1 activation is required for the transcription of ribosomal RNAs and ribosomal proteins (Hernández et al, 2009). Conversely, NF-Band CREB-dependent gene expression is required for learning and memory stabilization in mammals (Barco et al, 2002;Levenson et al, 2004b;Vecsey et al, 2007;Ahn et al, 2008;Fontán-Lozano et al, 2009) (for review, see Alberini, 2009). Our gene expression analysis in the hippocampus after OR training demonstrated the increase in NF-B and CREB gene targets and, in both cases, training-induced NF-B-and CREB-dependent gene expression required of PARP-1 activation.…”
Section: Discussionmentioning
confidence: 88%
“…PARP-1 regulates learning-induced gene expression by removing histone H1 from the promoters of cAMP response element-binding protein and nuclear factor-B target genes Histone H1 binds to nucleosome core particles near the entry/exit sites of linker DNA, influencing chromatin structure and gene regulation (Fan et al, 2005). It has been shown that learning consolidation requires the coordinated activation of the nuclear factor-B (NF-B) and cAMP response element-binding protein (CREB) transcription factors (Bozon et al, 2003;Ahn et al, 2008). The OR training session induced a twofold to fourfold increase in the expression of the NF-B target genes inducible nitric oxide synthase (i-nos) and tumor necrosis factor-␣ (tnf-␣), and in the CREB target genes c-fos, c-jun, and egr-1 in the hippocampus with respect to the untrained mice (for i-nos: 3.3 Ϯ 0.42-fold induction, t (8) ϭ 5.46, p Ͻ 0.001; for tnf-␣: 2.51 Ϯ 0.17-fold induction, t (8) ϭ 5.37, p ϭ 0.001; for c-fos: 2.41 Ϯ 0.45-fold induction, t (16) ϭ 2.6, p ϭ 0.018; for c-jun: 4.09 Ϯ 0.53-fold induction, t (16) ϭ 3.68, p Ͻ 0.001; and for egr-1: 4.78 Ϯ 0.38-fold induction, t (10) ϭ 4.78, p Ͻ 0.001) (Fig.…”
Section: Histone H1 Is Poly[adp]-ribosylated and Its Expression Decrementioning
confidence: 99%
“…Downstream of IkK, many target genes of the NFkB transcriptional complex contribute significantly to synaptic plasticity, such as NCAM, BDNF, opioid receptors, glutamate receptors, and neuregulin (Bunting et al, 2007;Chen et al, 2006;Frensing et al, 2008;Richter et al, 2002;Saha et al, 2006). Indeed, c-Rel, a member of the NFkB transcriptional complex, is required for long-term potentiation in the hippocampus (Ahn et al, 2008). Thus, IkK is capable of integrating many extracellular signals to alter gene expression and cause long-lasting changes in neuronal function and ultimately behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear factor B (NF-B) family of transcription factors has been shown to be required for memory formation and recall in a variety of learning paradigms in both invertebrate and mammalian systems (Freudenthal and Romano, 2000;Meffert et al, 2003;Kaltschmidt et al, 2006;O'Riordan et al, 2006;Ahn et al, 2008). Previous work indicates that neuronal NF-B promotes excitatory synaptic function in the mammalian CNS, which could underlie its role in learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Polo-like kinases (Plks) are a family of cell cycle-associated serine/threonine kinases that are co-opted in the brain to function in stabilizing changes in synaptic strength during homeostatic responses to prolonged activity. Plk2 and Plk3 family members are activity inducible and targeted to dendritic spines (Kauselmann et al, 1999;Pak and Sheng, 2003), where they promote synapse dismantling and downregulate neuronal activity (Pak and Sheng, 2003;Seeburg and Sheng, 2008;Seeburg et al, 2008) through phosphorylating proteins, including the postsynaptic spineassociated Rap GTPase-activating protein (SPAR; Pak and Sheng, 2003). Phosphorylation of SPAR leads to its degradation, which enhances overall Rap relative to opposing Ras activity, and promotes actin reorganization and dendritic spine loss, AMPAR internalization, and a depression of synaptic strength Zhu et al, 2002Zhu et al, , 2005Pak and Sheng, 2003;.…”
Section: Introductionmentioning
confidence: 99%